CDH23 Methylation Status and Presbycusis Risk in Elderly Women - Bouzid, Amal; Smeti, Ibtihel; Chakroun, Amine; Loukil, Salma; Gibriel, Abdullah Ahmed; Grati, Mhamed; Ghorbel, Abdelmonem; Masmoudi, Saber (Frontiers in Aging Neuroscience, 2018)
Introduction: Presbycusis, an age-related hearing impairment (ARHI) disease, is the most common cause for HI in adults worldwide. One of the best candidate genes for ARHI susceptibility is CDH23 which encodes stereocilia tip-links of the inner ear sensory hair cell. Although alterations in the methylation status of CpG dinucleotides across various genes were reported to be associated with HI, methylation changes in CDH23 gene have not been reported previously. Objectives: This study aimed at investigating whether DNA methylation level of CDH23 gene at intragenic CpG island overlapping an exonic-intronic region at position chr10:73565570-73565827 (GRCh37/hg19) could be risk factor associated with ARHI. Materials and Methods: We screened for methylation changes in this particular position for CDH23 gene in 50 blood samples of elderly women affected with presbycusis and healthy control cohort. Methylation of CpG sites were assessed using quantitative methylation-specific PCR following sodium bisulfite DNA conversion chemistry. Methylation levels were normalized against TSH2B reference gene. Results: DNA methylation analysis for the common CpG islands in CDH23 gene revealed 3.27-folds significant increase (p<0.0001) in methylation profile for ARHI women as compared to healthy controls with an elevated risk odds ratio of 2.219 [95% CI 1.071- 4.597]. Conclusion: Our study is the first of its kind to prove that higher CpG site methylation levels in CDH23 gene are likely to be associated with ARHI.